Arabic Language Learning Methods at the Raudhatun Najah Islamic Boarding School, Langsa City - Siti Radhiah (Al-Widad, 2023)
Every technique that experts have revealed has its advantages and disadvantages. This is a positive thing because they complement each other. Educators must have accuracy in determining the right method for students so that mistakes do not occur. Choosing the appropriate method for students is a very important first step to achieving success in teaching-learning. Conversely, errors in selecting methods by educators can be the initial cause of failure in achieving goals. The methodology in this study was to use qualitative field research conducted at the Raudhatun Najah Islamic Boarding School. In contrast, the research findings showed that at the Raudhatun Najah Islamic boarding school, students were asked to directly speak Arabic conversations without translating into their mother tongue. Although in practice, there are still many obstacles encountered. Some problems encountered at the Raudhatun Najah Islamic boarding school are the many words that need to be clarified for students, the lack of awareness of students to speak Arabic, and the lack of motivation from some teachers to create a good Arabic language environment. Arabic learning methods at the SMP/MTs level should focus on conversational aspects and everyday vocabulary mastery. This should continue to be practiced until students feel confident without having to focus too much on grammar from the start. After students feel comfortable speaking Arabic, then they are taught about grammar. It is important to remember that grammar in teaching Arabic is not an end but a tool to improve speaking and writing skills. This aspect of writing can be taught by asking students to write their everyday stories.